Seeking Academic Redemption: The Reconstruction of Learner Identity Among “Underprepared” Adults - Regina Smith; John M. Dirkx; Marilyn Amey (Adult Education Research Conference, 2002)
A desire to promote learning for personal development and change dominates much of research and practice in adult and higher education. Few studies, however, have attempted to describe how participating learners experience developmental programs, or how they make sense of these programs in the their particular life contexts. In this study, we describe the re-making of a “learner” identity, as narrated by underprepared adults enrolled in a developmentally-oriented community college program.